Religius-Rasional Ibnu Sina dan Relevansinya dengan Pendidikan Islam Kontemporer - Antin Rista Yuliani; Hasman Zhafiri Muhammad; Khofifah Hidayatuz Z; Adrian Adrian; Hamdan Arief Hanif (Nusantara: Jurnal Pendidikan Indonesia, 2023)
The purpose of this study is to analyze the educational thoughts of Ibn Sina and correlate them with contemporary Islamic education. The research methodology employed is literature review, utilizing secondary sources such as books, scholarly journals, dictionaries, documents, magazines, and others. The findings of this study reveal that Ibn Sina's educational ideas hold significant relevance to contemporary Islamic education. The research outcomes indicate that Ibn Sina was a polymath philosopher with expertise spanning various domains, including education. According to Ibn Sina, the purpose of education is characterized as universal, curricular, and operational. Ibn Sina categorized the curriculum based on the learners' age groups. Within Ibn Sina's pedagogical concept, several teaching methods are identified, including talqin (instruction), demonstration, habituation and exemplification, discussion, apprenticeship, assignments, encouragement, and discouragement. Ibn Sina also emphasizes the educator's role as a positive exemplar for the learners. The educational philosophies of Ibn Sina demonstrate relevance to contemporary Islamic education.